Kansas custom cattle feeding practices - Ted C. Schroeder; Gerry L. Kuhl (Kansas Agricultural Experiment Station Research Reports, 1988)
A survey of Kansas custom cattle feedlots was conducted in the fall of 1987. This paper summarizes the survey and discusses some of the custom cattle feeding services and charges being offered.
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-363-S; Cattlemen& #x27; s Day; 1988; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 539; Beef; Cattle feedlots; Feeding services